On the user’s side: definitions in Italian and British patient information leaflets - Pierini, Patrizia (Círculo de Lingüística Aplicada a la Comunicación, 2015)
This article examines patient information leaflets (PILs), as texts addressed by experts to laypersons. The PIL (foglio illustrativo in Italian) is a mandatory document packed with medicines that provide the patient with information about the medicine and instructions on how and when to take it. The paper comparatively analyses the definitions of medical terms in Italian and British PILs. It is based on a qualitative analysis of data extracted from two small comparable corpora consisting of 50 Italian and 50 British texts, respectively. Results have revealed some similarities that seem to be cross-cultural features of the genre, and significant differences.